Signals and images contributions and contradictions about high dilution research - Bonamin, Leoni Villano (Springer, 2008)
The GIRI - Groupe International de Recherche sur lA'Infinitesimal - was created in 1986 with the aim to gather researchers toward the high dilution questions, such as hormesis, isopathy, homeopathy and the phenomenological and conceptual differences among them. This book presents a portrait of the GIRI scientific activities